2019
DOI: 10.1136/jech-2018-211567
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adult height and type 2 diabetes mellitus: a systematic review and meta-analysis of observational studies

Abstract: BackgroundAlthough short adult height is generally associated with increased risks of type 2 diabetes mellitus (T2DM), there are large inconsistencies across studies. The aims of this study were to describe and quantify currently available evidence on the association between adult height and T2DM, to examine whether the reported associations differ by sex, and to examine the shapes of the height and T2DM associations.MethodsRelevant literature was identified using PubMed (1966–May 2018), EMBASE (1947–May 2018)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
(28 reference statements)
3
19
0
Order By: Relevance
“…Each standard deviation increase in height was associated with three times lower odds of T2D. This finding is consistent with a recent meta-analysis of 16 studies, which included one study from SSA (Nigeria), that reported an inverse association between height and T2D risk in both men and women [51]. However, a recent Mendelian randomisation study using European ancestry data found that the association between adulthood height and T2D did not persist after adjustment for BMI [52].…”
Section: Discussionsupporting
confidence: 88%
“…Each standard deviation increase in height was associated with three times lower odds of T2D. This finding is consistent with a recent meta-analysis of 16 studies, which included one study from SSA (Nigeria), that reported an inverse association between height and T2D risk in both men and women [51]. However, a recent Mendelian randomisation study using European ancestry data found that the association between adulthood height and T2D did not persist after adjustment for BMI [52].…”
Section: Discussionsupporting
confidence: 88%
“…To that end, the association of waist circumference and type 2 diabetes is now well-established [6]. Other anthropometric indexes such as height [7], body circumferences [8] and body fat distribution [9] have been associated with type 2 diabetes to varying extent across the global populations.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many global studies have suggested that short adult height is generally associated with an increased risk of development of T2DM. 4 Relationships have been described between BMI and glycaemic control, but no studies were found, to our knowledge, on the association between adult height and glycaemic control in PLWD. In Soweto, South Africa (SA), Khoza et al 5 assessed the effect of HIV on glycaemia and renal function in patients with T2DM; however, no mention was made of any relationship between glycaemic control and patient height.…”
Section: Introductionmentioning
confidence: 80%